Effect of 30˚C Electrolyte Temperature on The Sensitivity Cu/Ni - Toifur, Moh.; Islamiyati, Rizka Nuzul (Program Studi Fisika Universitas Negeri Jakarta, 2024)
Given the necessity of cryogenic storage and monitoring cryogenic temperatures is equally important. This study aims to determine the resistance value and sensitivity of copper wire before and after electroplating at 30˚C electrolyte temperature as a low temperature sensor. The electrolyte solution consists of NiSO4 260 g, NiCl2 60 g, H3BO3 40 g and Aquades 1000 mL. Electroplating was carried out with an electrolyte temperature of 30˚C, electrode distance of 4 cm, voltage of 4.5 volts and plating time of 4 minutes. The plating results were analyzed to determine the resistance and sensitivity of the sensor at temperatures from 0 to -160˚C. The results showed that the resistance value of the Cu coil obtained RCu = (1.44 ± 0.00) ohm and the resistance of the Cu/Ni coil RCu / Ni = (1.50 ± 0.00) ohm. The resistance value on the Cu/Ni coil (after plating) is greater than the Cu coil (before plating). While the test results of sensor sensitivity show that Cu and Cu/Ni coils have properties as low temperature sensors. Sensor sensitivity increases after plating. The sensitivity value obtained by Cu coil is S(T) = -1E-06T + 6E-05 and Cu/Ni coil S(T) = -2E-06T + 2E-05. The projection sensitivity at a temperature of -200 ˚C obtained is 0.00046 V/˚C less than the Cu/Ni coil 0.00082 V/˚C. So nickel plating on copper coil at 30˚C electrolyte temperature has successfully improved the sensitivity value of the low-temperature sensor.